2009
DOI: 10.1063/1.3073994
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and phonon dynamics in NiPdSi: An annealing study by temperature-dependent Raman spectroscopy

Abstract: We have demonstrated the effective Raman spectroscopy for the phase transition and phonon dynamics of NiPdSi films annealed at various temperatures. In addition to the appearance of alloy disorder-induced Raman peaks, we have shown that the presence of Pd in NiSi results not only in the retardation of NiSi2 phase transition to about 900 °C, but also in the redshift (∼3–4 cm−1) of the first-order Raman peaks. The observed Raman frequency downshift with increasing temperature can be described well by a model whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…These two peaks confirm the formation of NiSi NWs on the Ni foam substrates [23][24][25]. As indicated in figure 2(e), the strongest peak at 214 cm −1 and weak peaks at 362 and 289 cm −1 belong to the A g modes of NiSi [26,27]. The second strongest peak at 196 cm −1 and the weak peak at 254 cm −1 are assigned to the B 1g and B 2g modes of NiSi, respectively [24].…”
Section: Methodssupporting
confidence: 64%
“…These two peaks confirm the formation of NiSi NWs on the Ni foam substrates [23][24][25]. As indicated in figure 2(e), the strongest peak at 214 cm −1 and weak peaks at 362 and 289 cm −1 belong to the A g modes of NiSi [26,27]. The second strongest peak at 196 cm −1 and the weak peak at 254 cm −1 are assigned to the B 1g and B 2g modes of NiSi, respectively [24].…”
Section: Methodssupporting
confidence: 64%
“…24,25 The peak at 217, 294, and 363 cm À1 are assigned to A g mode whereas 199 cm À1 assigned to the B 1g mode. 26 A slight sift ($1 cm À1 ) of peak compared to as reported by the Karabko et al 26 has been observed. A small shoulder peak observed at 371 cm À1 is attributed to a formation of NiSi 2 phase in the film.…”
Section: A Materials Characterizationsmentioning
confidence: 63%
“…Representative MRS spectra are shown in Fig. 10,11 Further increasing x to 0.5 (curve C), decreasing t to 1 nm (curve D), or increasing T RTP to 550 C (curve E) leads to the disappearance of this peak. Starting with x ¼ 0, t ¼ 2 nm, and T RTP ¼ 500 C, the characteristic MRS peak at 204 cm À1 (curve A) is indicative of the formation of CoSi.…”
Section: Resultsmentioning
confidence: 98%